2020
DOI: 10.1016/j.ces.2019.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of two-step redox recycling of non-stoichiometric ceria with thermochemical dissociation of CO2/H2O in moving bed reactors – Part I: Model development with redox kinetics and sensitivity analysis

Abstract: Chemical looping syngas production is a two-step process that produces CO and H2 from water and CO2 splitting. This is performed by exploiting a metal oxide as oxygen carrier material, which is thermally reduced and releases oxygen in a subsequent step. The core-process layout is composed of two reactors (oxidation reaction and reduction reactor) and oxygen carriers (metal oxides) circulating between the two reactors. A comprehensive moving-bed reactor model is developed and applied to simulate both the syngas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…By using FORTRAN and ASPEN Plus ® , Farooqui et al [89] simulated TR and combined WS and CDS steps of the ceria-driven redox cycles by developing and using a moving-bed reactor model. Simulation results indicated that 0.198 of non-stoichiometry can be achieved in ceria during the TR step at 1600 • C and 10 −7 bar vacuum pressure.…”
Section: Year 2020mentioning
confidence: 99%
“…By using FORTRAN and ASPEN Plus ® , Farooqui et al [89] simulated TR and combined WS and CDS steps of the ceria-driven redox cycles by developing and using a moving-bed reactor model. Simulation results indicated that 0.198 of non-stoichiometry can be achieved in ceria during the TR step at 1600 • C and 10 −7 bar vacuum pressure.…”
Section: Year 2020mentioning
confidence: 99%
“…The importance of thermochemical cycles in producing synthetic fuels has significantly increased with the approved worldwide climate protocols [4]. One of the most effective thermochemical cycles is the two-step redox oxide pair system, which has shown great potential for synthetic solar fuel generation [5]. The principle of operation is based on the transition between the higher valence oxidized and lower valence reduced form of the oxide of a metal having multiple oxidation states [6].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the understanding of operability of fluidized bed reactors, a huge volume of gas is required for the fluidization, and this would certainly decrease the selectivity of the CO and H2 produced to very low values, which limits the application of fluidized bed reactor for oxidation. Therefore, in the present layout, a moving bed reactor has been considered for the oxidation (as reported in [229]). The beam down reactor configuration seems to be easier to operate, especially with regards to solids handling between the reduction and the oxidation reactor.…”
Section: Power Plant Layout and Configurationmentioning
confidence: 99%
“…2. Reduction (RED) and oxidation reactors (OXI) are modelled as moving bed reactors as presented in our parallel work [229]. 3.…”
Section: Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation